Translation Procedures of Phrasal Verbs in Breaking Dawn Novel - Muhammad Muslim Nasution; Anni Holila Pulungan (LINGUISTIK TERAPAN, 2016)
The objective of this study were (1) to describe types of phrasal verbs occurring in translating Breaking Dawn Novel (2) to describe procedures are used in translating Breaking Dawn Novel  (3) to find out the most dominant phrasal verbs and procedures used in translating Breaking Dawn Novel. The data were phrasal verbs obtained from clause of Breaking Dawn novel. This research applied qualitative research design. The data were collected through documentary technique. The findings of this study showed that: 1) All of phrasal verbs were found in Breaking Dawn novel, they are type 1, type 2, type 3 and type 4,  2) there were six procedures used in translating phrasal verbs, they are Calque (8 data), Literal translation (35 data), transposition (107 data), modulation (82 data), equivalence (11 data), and Adaptation (3 data), 3) the dominant phrasal verbs occurred in Breaking Dawn novel was type 3 and the dominant procedures used in translating Breaking Dawn novel was transposition procedure. Keywords: translation procedures, phrasal verbs, novel